A Phenomenological Study on the Experiences of Parenting Burden of Working Mother with Young Children in Korea - Na Hyun Kim; Eun Joo Lee; Su Young Kwak; Mee Ra Park (Korean Journal of Women Health Nursing, 2013)
PURPOSE: The purpose of this study was to describe the essential structure of the lived experience of working mothers' parenting burden in Korea. METHODS: Eight working mothers with young children were interviewed. The Colaizzi analysis of phenomenological research was applied. RESULTS: Seven theme clusters were extracted: a life with constant conflict, sense of guilt, feeling anxious because of lack of information about education for their children, social stigma as a deficient mother, family relationship becoming distant, a life being exhausted, day to day struggle. CONCLUSION: These results provide an opportunity to have a better understanding of the experiences of working mothers related to parenting their young children. It would also serve as a medium for the formulation of appropriate nursing intervention relevant to burdens of parenthood.